C.E. Credit. Truth Decay and Tooth Decay: The Role of Dental Teams in Sharing the Science of Community Water Fluoridation - Tooka Zokaie; Matt Jacob; Howard Franklin Pollick (Journal of the California Dental Association)
Background The benefits and safety of community water fluoridation (CWF) are well-established with over eight decades of research. Yet, some communities have ceased CWF due to mistrust in the safety of this program. Public health infrastructure faces a challenge in addressing misinformation and fostering trust in evidence-based recommendation. Understanding individual decision-making can offer clues for why some people in our communities are not comfortable with public health programs. A review of recent data shows the role of dental care providers as trusted leaders in health information in a culture of doubt.Conclusion The role of dental providers as trusted leaders requires that they be supported with evidence-based resources. These resources can strengthen their ability to educate patients about the benefits and safety of CWF. Dental providers can build trust in CWF by learning the history of CWF research, addressing concerns about drinking public water, and integrating toolkits to build health literacy and confidence with personal health decision-making. Dental team members can build confidence by sharing the safety and benefits of community water fluoridation. Building comfort in drinking public tap water and fluoridation programs can strengthen population health practices.Continuing Education Credit Available The practice worksheet is available online in the supplemental material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.